2017
DOI: 10.1101/232868
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Female grant applicants are equally successful when peer reviewers assess the science, but not when they assess the scientist

Abstract: Background: Funding agencies around the world show gender gaps in grant success, with women often receiving less funding than men. However, these studies have been observational and some have not accounted for potential confounding variables, making it difficult to draw robust conclusions about whether gaps were due to bias or to other factors. In 2014, the Canadian Institutes of Health Research (CIHR) phased out traditional investigator-initiated programs and created a natural experiment by dividing all inves… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
16
0
1

Year Published

2018
2018
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 101 publications
0
16
0
1
Order By: Relevance
“…Analyses of success rates have yielded mixed results in terms of 22 the presence and magnitude of such inequities. Some analyses have found lower success rates for 23 female-authored papers [17,18] and grant applications [19,20], while other studies have found no 24 gender differences in review outcomes (for examples, see [21][22][23][24][25]). Inequities in journal success 25 rates based on authors' nationalities or country of affiliation have also been documented, with 26 reports that authors from English-speaking and scientifically-advanced countries have higher 27 success rates [26,27]; however, other studies found no evidence that the language or country of 28 affiliation of an author influences peer review outcomes [27][28][29].…”
mentioning
confidence: 99%
“…Analyses of success rates have yielded mixed results in terms of 22 the presence and magnitude of such inequities. Some analyses have found lower success rates for 23 female-authored papers [17,18] and grant applications [19,20], while other studies have found no 24 gender differences in review outcomes (for examples, see [21][22][23][24][25]). Inequities in journal success 25 rates based on authors' nationalities or country of affiliation have also been documented, with 26 reports that authors from English-speaking and scientifically-advanced countries have higher 27 success rates [26,27]; however, other studies found no evidence that the language or country of 28 affiliation of an author influences peer review outcomes [27][28][29].…”
mentioning
confidence: 99%
“…An important question for modern cognitive science is whether there is gender disparity in opportunity and advancement over the professional lifespan (Ceci, Ginther, Kahn, & Williams, 2014;Geraci, Balsis, & Busch, 2015;Valian, 1998). Certainly, attitudes about women's career roles in STEM (i.e., science, technology, engineering, & medicine), and educational/career trajectories have evolved compared to generations past (Cundiff, 2012).…”
mentioning
confidence: 99%
“…Certainly, attitudes about women's career roles in STEM (i.e., science, technology, engineering, & medicine), and educational/career trajectories have evolved compared to generations past (Cundiff, 2012). Such improvements have occasionally sparked doubts as to whether a gender parity problem still exists (e.g., Ceci, Ginther, Kahn, & Williams, 2014), a sentiment that is potentially exacerbated by notions of academic meritocracy, and limited awareness about the influence of implicit gender schemas on everyday behavior (Valian, 1998). However, varied sources of evidence indicate that academia has not attained gender parity (Cundiff, 2012, Hill, Corbett, & St. Rose, 2010Duch, Zeng, Sales-Pardo, Radicchi, Otis, & Woodruff, 2012;Kite, Felipe Russo, Brehm, Fouad, Hall, Hyde, & Keita, 2001;Morawski & Agronick, 1991), even within disciplines viewed as "feminized," such as psychology (e.g., Vaid & Geraci, 2016).…”
mentioning
confidence: 99%
“…Wellcome explained that this was “attributable to less favorable assessments of women as principal investigators, not differences in assessments of the quality of science led by women.”23…”
Section: Extreme Bias In Research Fundingmentioning
confidence: 99%